(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2022)
Put call parity is the no arbitrage condition which must hold true for an efficient financial market. The present study examines the Indian stock market efficiency by using different option contracts for about 400 observations during three consecutive months. Deviation in PCP model provides opportunity to earn abnormal profits to arbitrageur. Three different scenarios have been considered for testing the PCP model. Our result in all scenarios shows the mispricing in the Indian stock market. The empirical analysis provides the level of profit which can be made by arbitrageur. The findings show that Indian stock market as inefficient market.